Unraveling Legal Frontiers: Online Workforce Dynamics and Regulatory Challenges - Satrio, Bram; Rosnawati, Emy (Proceedings of The ICECRS, 2023)
In this study, we examine the multifaceted landscape of online business workforces, encompassing roles in website development, marketing, sales, and customer service within internet-based companies. Investigating both on-site and remote work scenarios enabled by communication technologies, our research aimed to analyze legal dimensions such as employment contracts, wages, copyrights, and information security in online businesses. Through comprehensive qualitative and quantitative methods, we elucidated the intricacies of this digital labor sphere. Our results reveal evolving work patterns and the critical significance of adaptable legal frameworks in ensuring fair labor practices in online environments. The implications of this research underscore the imperative for global policymakers and businesses to craft agile strategies, emphasizing a balance between innovation and labor rights protection in the ever-expanding digital workspace. Highlights : Comprehensive Analysis: This study provides a thorough examination of the roles and legal aspects within online business workforces, offering a comprehensive understanding of the digital labor landscape. Evolving Work Patterns: The research uncovers shifting work patterns, emphasizing the need for adaptable legal frameworks to ensure fair labor practices amidst technological advancements. Global Implications: The findings stress the global significance, urging policymakers and businesses worldwide to develop agile strategies that harmonize innovation with safeguarding labor rights in the dynamic digital workspace. Keywords: Online business, Workforce dynamics, Legal dimensions, Digital labor sphere, Labor rights protection.